Causal Relationships and Short-Term Dynamics Between Oil Price and Stock Market Returns in Malaysia - Rasheed, Arif; Saeedi, Mitra; Gebril, Nalini; Hariraj, Kumaraseh (International Journal of Psychosocial Rehabilitation, 2020)
This study aims to corroborate the individual and institutional insights of the relationship between oil price and stock returns in Malaysia to cultivate a comprehensive policy instrument. It endeavors to analyze the causal relationships and short-term dynamics between oil price and stock return in Malaysia from 2006 to 2016. The Granger Causality approach is performed to analyze the causal relationships, and Impulse Response Function (IRF) within Vector Auto Regression (VAR) models is used to identify the short-run dynamic among the stock index series with oil price. The results determine that oil price movements do not affect the Granger-cause aggregate market index. However, unidirectional and bidirectional causality exists among other selected indices and oil price. The results also show a positive short-run dynamic among individual sector returns and oil price; though, the Malaysian stock market index does not seem to respond immediately to oil price shocks.